2020
DOI: 10.1002/btm2.10195
|View full text |Cite
|
Sign up to set email alerts
|

Microscopy‐guided laser ablation for the creation of complex skin models with folliculoid appendages

Abstract: Engineering complex tissues requires the use of advanced biofabrication techniques that allow the replication of the tissue's 3D microenvironment, architecture and cellular interactions. In the case of skin, the most successful strategies to introduce the complexity of hair follicle (HF) appendages have highlighted the importance of facilitating direct interaction between dermal papilla (DP) cells and keratinocytes (KCs) in organotypic skin models. In this work, we took advantage of microscopy‐guided laser abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…IHC markers K10, K14, K15, fibronectin, vimentin, involucrin, and β-catenin confirmed that the keratinocytes infiltrated the biofabricated channels, and a structure resembling an immature hair bulb formed. However, there was no hair shaft formation …”
Section: Layer-by-layer Analysis Of Skin Tissue Modelsmentioning
confidence: 99%
“…IHC markers K10, K14, K15, fibronectin, vimentin, involucrin, and β-catenin confirmed that the keratinocytes infiltrated the biofabricated channels, and a structure resembling an immature hair bulb formed. However, there was no hair shaft formation …”
Section: Layer-by-layer Analysis Of Skin Tissue Modelsmentioning
confidence: 99%
“…The system also directed the interaction between keratinocyte and DPCs to reconstruct the HF structure. 138 Human keratinocytes derived from outer root sheath cells and DPCs cultured in Matrigel (3D network of ECM proteins and collagen) form tubule-like structures in the skin in vitro. They organize into epidermal-like cyst-like spheres rather than form the intact HFs.…”
Section: Homeostatic Construction Of Hf Organoids Via a Biomaterials ...mentioning
confidence: 99%
“…Abreu et al used microscopy-guided laser ablation to microprocess fibroblast-filled collagen hydrogels and create a sub compartment to guide the migration of keratinocyte. The system also directed the interaction between keratinocyte and DPCs to reconstruct the HF structure . Human keratinocytes derived from outer root sheath cells and DPCs cultured in Matrigel (3D network of ECM proteins and collagen) form tubule-like structures in the skin in vitro.…”
Section: Homeostatic Construction Of Hf Organoids Via a Biomaterials ...mentioning
confidence: 99%
“…While epithelial invagination and formation of an epithelial column are required for HF morphogenesis, DP spheroids rapidly dissociate when placed within collagen matrices 83 , which might be compromising DP cell inductivity and model progression. Bearing this in mind, we were able to create a more complex skin model with folliculoid appendages by incorporating, within the dermal equivalent layers, aggregates with compartmentalized DP cells and keratinocytes 161 . Microscopy-guided laser ablation was used to fabricate a channel connecting the constructs' surface and the aggregates, to support epithelial cell migration.…”
Section: Developments In the Bioengineering Of Human Hair Follicle Modelsmentioning
confidence: 99%
“…Bearing this in mind, we were able to create a more complex skin model with folliculoid appendages by incorporating, within the dermal equivalent layers, aggregates with compartmentalized DP cells and keratinocytes. 161 Microscopy‐guided laser ablation was used to fabricate a channel connecting the constructs' surface and the aggregates, to support epithelial cell migration. Follicle‐like structures with differenced concentric epithelial layers and mimicking the hair bulb architecture were obtained, though a hair shaft was not formed.…”
Section: Developments In the Bioengineering Of Human Hf Modelsmentioning
confidence: 99%